Advanced Fluorescence Reporters in Chemistry and Biology III Applications in Sensing and Imaging - Demchenko, A. P. (Aleksandr Petrovich); Callis, P. R. (aSpringer Series on Fluorescence, Methods and Applications, 2011)
The key element of any fluorescence sensing or imaging technology is the fluorescence reporter, which transforms the information on molecular interactions and dynamics into measurable signals of fluorescence emission. This book, written by a team of frontline researchers, demonstrates the broad field of applications of fluorescence reporters, starting from nanoscopic properties of materials, such as self-assembled thin films, polymers and ionic liquids, through biological macromolecules and further to living cell, tissue and body imaging. Basic information on obtaining and interpreting experimental data is presented and recent progress in these practically important areas is highlighted. The book is addressed to a broad interdisciplinary audience.